O empoderamento das mulheres ribeirinhas por meio ingresso da Universidade de Tefé - França, Deize Martins (2024)
This dissertation aims to analyze the role of the University in the lives of riverside women and how they made this education a means to improve their lives and, consequently, empower themselves as women, through education. This dissertation consists of qualitative research, with a case study, with the participation of the University of the State of Amazonas, the Centro de Estudos Superior de Tefé, riverside women who had their time at the University and who brought new knowledge and collaboration to their communities. For the case study, four women participated, currently graduates and teachers in the municipal education network, in which the main purpose was to show their learning trajectory, both at the university and in everyday life in their community, since childhood. to the present day, through semi-structured interviews, presenting the following aspects: the first is the presentation of these women, showing their reality since childhood in the community, their learning, work and family structure, the second is showing the contributions of university to the community and specifically the research interlocutors and finally, to show the achievements of these women through their academic training. For this study, we guided the theoretical aspects based on contributions from authors such as: Geertz (1989), Bourdieu (2007), Freire (2003), Woortman (2010), Joice Berth (2019). In this study, it was possible to understand how academic training enabled riverside women, in this specific work, to change their lives through education, understanding but highlightingthat public policies are essential for their permanence at University. flawed for this public.